ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH: STUDI KASUS DI PROVINSI SUMATERA UTARA PERIODE 2019-2022 - Jhoni F. Manurung; Fidia C. Sitorus; Pawer D. Panjaitan; Fadilah R. M. Siregar; Elsa D. Naibaho (MANAJEMEN, 2024)
The purpose of this study was to determine the level of financial performance of the North Sumatra government. The example used is the Budget Realization Report of North Sumatra Province 2019-2022. The analysis method uses five types of indicators, namely: regional financial independence ratio, effectiveness ratio, growth ratio, harmony ratio, and fiscal decentralization ratio. The data collection method is done by taking data from the BPS (Central Bureau of Statistics) website of North Sumatra. The results showed that the ratio of regional financial independence in the financial statements of North Sumatra province has a delegative pattern, while the effectiveness ratio is in the ineffective area. Other results show that the growth ratio is fluctuating, the harmony ratio is in an unbalanced condition, and the fiscal decentralization ratio is in the high category.